Mind the gap: Sustainable management of the surging plastic waste in the post-COVID-19 pandemic - Zhu, Minghai; Huang, Qing (Frontiers in Environmental Science, 2025)
The outbreak of COVID-19 inevitably boosted the global consumption of personal protective equipment (PPE), including face masks, gloves, and protective clothes. While wearing PPE could protect the public health from the transmission of infectious diseases, a concern draws attention on the environmental issues of plastic waste. This review examines the dual challenges of managing pandemic-associated plastic waste and mitigating the ecological and health risks posed by micro- and nanoplastics (MNPs). The results showed that the traditional technologies including landfilling and incineration accounted for around 40% and 25%, respectively. The incineration could reduce over 90% of the waste volume, but release MNPs or byproducts. Circular economy strategies—guided by reduce, reuse, and recycle principles—offer promising alternatives, particularly advanced thermochemical recycling that converts waste into value-added chemicals. For PPE, disinfection prior to reuse is of great necessity, including incineration (>800°C), chemical disinfection (ozone, H2O2), or physical methods (steam, microwaves). Although sorption and filtration strategies could remove the MNPs with over 99% efficiency, they are still in the lab-scale. Biological solutions—such as bacteria, enzyme, and worms—demonstrate potential for degrading synthetic polymers. This work underscores the urgency of integrating circular economy frameworks and tried to submit a comprehensive proposal to reduce the plastic waste, which could finally reduce the environmental burden brought by the COVID-19 pandemic.